Social Networks and Barriers to ART Adherence Among Young Adults (18–24 years) Living with HIV at Selected Primary Health Facilities of South-Western Uganda: A Qualitative Study - Ajuna N (Dove Medical Press, 2021)
Noble Ajuna,1 Brian Tumusiime,1 Joseph Amanya,1 Sharon Awori,1 Godfrey Z Rukundo,2 John Baptist Asiimwe1 1Department of Nursing, Bishop Stuart University, Mbarara City, Southwestern Uganda; 2Department of Psychiatry, Mbarara University of Science and Technology, Mbarara City, Southwestern UgandaCorrespondence: John Baptist Asiimwe Tel +256 775979015; +256 751300773Email johnbaptistasiimwe.2008@gmail.comBackground: Young adults living with HIV (YALWH) struggle to maintain high levels of adherence to antiretroviral therapy (ART) because of numerous barriers. This study describes the social networks of YALWH (18– 24 years), their barriers to ART adherence, and the perceived role of social networks in overcoming those barriers.Methods: This study used a qualitative descriptive research design. Twenty-three (23) YALWH who were on ART for a period of greater than one (1) month and had consented to participate in the study were purposively selected from two primary health care facilities in southwestern Uganda. We held four (4) focus group discussions with the YALWH over 5 weeks between the 24th of July and 7th September 2020. Data were audio recorded, transcribed, and entered in Microsoft word 2010. Using the content analysis techniques, data were inductively coded and categories or themes developed.Results: Most YALWH belonged to bonding (family, friends, and neighbors), followed by bridging (informal groups), and linking (health professionals) social networks, respectively. Most YALWH, irrespective of gender, had close connections with their mothers or elder sisters. The commonest form of bridging networks was informal community groups that provided financial services, whereas the linking ones comprised health professionals’ directly involved in HIV patient care such as nurses, counselors, and their affiliates (expert clients or clinic based peer supporters), who occasionally acted as bonding networks. Structural barriers to ART adherence (eg, stigma) were the most cited, followed by medication- (eg, pill burden), and patient-related barriers (eg, non-disclosure of HIV status). Bonding networks were perceived to help overcome patient, medication, and structural barriers to ART adherence. Bridging networks overcame structural and medication-related barriers to ART adherence. Linking networks were perceived to help overcome some health systems and medication-related barriers to ART adherence.Conclusion: Bonding social networks seem to play a prominent role in overcoming numerous barriers to ART adherence compared with bridging and linking social networks.Keywords: HIV, ART adherence, barriers, social networks, YALWH, perceived role